The Impact of Green Innovation Orientation on Enhancing Competitive Advantage of Private Universities: A Perspective from Graduates of OnaizahColleges, Saudi Arabia - Mahmoud Kamal Moussaّ,; Zuheir Mohamed Kamal, (Journal of North African Economies, 2025)
The aim of this research is to investigate how focusing on green innovation principles influences the competitive advantage of private universities, as perceived by graduates of OnaizahColleges in the Kingdom of Saudi Arabia. The study utilized a descriptive-analytical approach and surveyed 150 graduates from Onaizah Colleges between 2020 and 2023. Data was collected using Google Forms, and statistical analysis was conducted using SPSS software, including descriptive measures and simple linear regression. The findings of the study revealed a significant positive impact of green innovation dimensions within Onaizah Colleges on enhancing the competitive advantage, according to the graduates' perspective. Based on these findings, the study provides recommendations to help colleges enhance their focus on green innovation and strengthen their competitive advantage, ultimately achieving distinction among universities. These recommendations include integrating green innovation into educational programs and research activities, as well as implementing effective marketing strategies to raise awareness about green innovation initiatives and their associated competitive advantages.